2019
DOI: 10.1080/13218719.2018.1506714
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Psychosocial Characteristics and Offense Patterns in Females with Online Child Pornography Offenses

Abstract: Despite a growing body of literature on females who sexually offend, there is a dearth of research on online sexual offending in women. This study collected descriptive psychosocial and offense conduct data on 98 females convicted of online sexual offenses housed in United States federal prisons. Psychosocial history results demonstrated that 60% of the subjects reported a history of sexual abuse (n ¼ 59), while 46% reported physical abuse (n ¼ 45). In addition, 47% reported a history of outpatient mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…There are also overlaps between offenders who produce and/or distribute CSAM and those who engage in contact (sexual) offending (Bickart et al 2019;Bissias et al 2016;Bouhours & Broadhurst 2011;Gewirtz-Meydan et al 2018;McManus et al 2015;Shelton et al 2016;Wolak, Finkelhor, Mitchell & Jones 2011). McManus and colleagues (2015) found that CSAM offenders (ie producers, distributors, and distributors/possessors) who had previously committed a sexual offence against a child were over seven times more likely to have produced CSAM than those with no previous history of contact sexual offences.…”
Section: Offender Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are also overlaps between offenders who produce and/or distribute CSAM and those who engage in contact (sexual) offending (Bickart et al 2019;Bissias et al 2016;Bouhours & Broadhurst 2011;Gewirtz-Meydan et al 2018;McManus et al 2015;Shelton et al 2016;Wolak, Finkelhor, Mitchell & Jones 2011). McManus and colleagues (2015) found that CSAM offenders (ie producers, distributors, and distributors/possessors) who had previously committed a sexual offence against a child were over seven times more likely to have produced CSAM than those with no previous history of contact sexual offences.…”
Section: Offender Characteristicsmentioning
confidence: 99%
“…For some offenders, contact sexual abuse represents a necessary part of the CSAM production process (see Bickart et al 2019;Gewirtz-Meydan et al 2018;McManus et al 2015;Sheehan & Sullivan 2010). However, some producers of CSAM do so strictly online through the use of webcams, and thus do not themselves perpetrate contact sexual abuse (McManus et al 2015).…”
Section: Offender Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations